(untitled) (AFRICAN JOURNAL OF APPLIED RESEARCH, 2025)
Purpose: Polluted soils have a negative impact on agricultural crop yield and food safety; hence, they are a global concern. A wet battery waste disposal area has been encroached due to farmers’ attempts to increase productivity in the research area. The farmers’ desire to expand productivity inspired this study, which assessed the impact of battery waste deposits at different spatial scales on the evenness and richness of beneficial microorganisms. Design/Methodology/Approach: Twenty (20) points were randomly sampled from the non-contaminated site, the main battery dumpsite (MDS), and 20 and 40 m away from the MDS. The study adopted a factorial arrangement on a completely randomised design that was replicated three times. Analysis of variance was used to analyse the data, and microbiological analyses were conducted within the experiment. Where means were significant, Duncan’s multiple range test separated them. Findings: Glomus had the highest count of 144.3-fold in 20 MA, while Acaulospora and Funneliformis were significantly and predominantly abundant in 40 MA by 282.0 and 55-fold, respectively.MDS had significantly the lowest or least numerical values in most AMF species across all the spatial distances Research Limitation: The work focused on an abandoned dumpsite by a defunct battery manufacturing company. Practical Implication: For marginally contaminated areas, the findings can guide the selection of appropriate crops and associated beneficial microbes that minimise heavy metal uptake, enabling safer productive use of remediated lands. Social Implication: This research can help identify whether harmful metals are becoming more bioavailable over time or being naturally immobilised, directly impacting health risk assessments for vulnerable populations. Originality / Value: This research significantly advances our understanding of how complex microbial communities respond to and potentially mitigate the extreme environmental conditions created by battery waste.